Study of a New Design of the Planar Inverted-F Antenna for Mobile Phone Handset Applications - Ghnimi, S.; Nasri, A.; Gharsallah, A. (Engineering, Technology & Applied Science Research, 2020)
This paper suggests a new design of the PIFA antenna for mobile phone handset applications. In this context, we are interested in the development of new techniques based on the creation of slot matching for the improvement and miniaturization of a dual-band PIFA antenna operating at 900MHz and 1800MHz. Analysis of antenna parameters such as return loss (S11), radiation pattern, Voltage Standing Wave Ratio (VSWR), current distributions, gain, and the relation between them are performed in CST software. There is a good agreement between the results of simulation by CST and HFSS and those of measurement for the proposed antenna.